EVALUATION OF THE IMPLEMENTATION OF OCCUPATIONAL HEALTH, SAFETY, AND ENVIRONMENTAL (OHSE) MANAGEMENT SYSTEM IN HIGHER EDUCATION LABORATORIES: A CASE STUDY OF THE ANALYTICAL CHEMISTRY LABORATORY, STATE POLYTECHNIC OF LHOKSEUMAWE - Fitriah, Nurul (Jurnal Sains dan Teknologi Reaksi, 2024)
Occupational Health and Safety (OHS) is a crucial aspect in ensuring safe laboratory operations, both in academic and research settings. Laboratory risks include exposure to hazardous chemicals, physical hazards, and behavioral negligence that may lead to workplace accidents. This study aims to evaluate the implementation of OHS in the Analytical Chemistry Laboratory of the State Polytechnic of Lhokseumawe, with a focus on safety policies, compliance with the use of personal protective equipment (PPE), risk perception, and safety culture. The research employed a descriptive quantitative approach through observations, checklist assessments, and brief interviews with laboratory users. The evaluation results indicate that OHS implementation has been carried out but remains suboptimal; aspects such as safety facilities, planning, and management involvement still require improvement. These findings are consistent with the literature emphasizing the importance of risk management, safety culture, and continuous supervision in laboratories. Recommendations include strengthening training, enhancing technician supervision, and providing adequate OHS facilities to minimize the potential for workplace accidents. Keywords: OHSE, laboratory, risk management, safety culture, OHS implementation